PERAN AKUNTAN DALAM MENGHADAPI DIGITALISASI EKONOMI MENJELANG ERA SOCIETY 5.0 - Cakra Dewa, Monica Malva; Yunia Kharisyami, Putu Widya; Diva Navael, Lovenka; Maulana, Agus; Agus Maulana (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
The digitalization of the economy toward the Society 5.0 era has begun to be realized in Indonesia. The era of Society 5.0 is shown by all the facilities obtained by humans through systems, technology, and robots. The existence of an accountant in the era of Society 5.0 is expected to decrease. This study aims to determine the description of the accounting profession in the era of Society 5.0 and efforts that can be made by an accountant in dealing with that era. This study uses a qualitative approach research method with data collection techniques derived from literature review. The results of this study indicate differences in the practice of accountants in the past and the era towards Society 5.0. Accountants' task has become more effective and efficient because of the digitalization of the economy. Era Society 5.0 also provides opportunities and challenges for accountants. Therefore, an accountant requires skills in the field of information technology in order to survive in the era of Society 5.0 and following eras.